The 'codification' of governance in the non-profit sport sector in the UK. Issue 4 (8th August 2018) - Walters, Geoff; Tacon, Richard
ABSTRACT: Research question : Codes of governance have proliferated in recent years, yet academic research on why boards adopt and implement codes remains limited. This research focuses on the non-profit sport sector in the UK and looks at why codes have been adopted by a board of a non-profit sport organisation. Research methods : The research draws on a longitudinal case study of board processes in a national governing body of sport in the UK, drawing on non-participant observation of board and committee meetings, interviews and document analysis. Results and findings : We identify that the initial adoption of a code of governance is a way to create external legitimacy. Once adopted, a code of governance can strengthen the internal legitimacy and reinforce board members' perceptions that the board is well governed. These two processes of legitimising are mutually reinforcing, serving to ensure that codes of governance become institutionalised at the board level. At the same time, while codes typically emphasise the importance of board members making autonomous decisions, in our case board members perceived that codes often constrained board autonomy. Implications : This is the first article to provide an 'insider', board-level perspective on code adoption in the non-profit sport sector. It also enhances debate on the role of legitimacy in code adoption, by distinguishing between external legitimising as a formal, impersonal process, and internal legitimising, which typically unfolds through discussion, negotiation and reflection.